(untitled) (Economic and Political Thought, 2018)
As a result of its own strategy, gradual development, vertical integration or other factors, a firm may experience employing a worker with some firm-specific human capital. This situation implies a kind of interdependence between the employer and the employee whose knowledge and abilities can be perceived as a specific asset. Both parties become strongly interdependent: the employer has to rely on the employee and, on the other hand, the employee cannot change his workplace easily. The presented relations are compared to a bilateral monopoly situation in order to examine the possibility of using analogous research tools. This paper identifies difficulties accompanying the functioning of the firm, when the core business is based on firm-specific human capital and contains solutions referring to transaction costs economics and the agency theory.